O papel da prosódia na ironia como expressão de atitude - Karen Maria de Paula (2012)
The speech not only conveys strictly linguistic content of the sentences, but also the expression of attitudes and emotions of the speaker. In this context, prosody plays an important role, which may result in adding information to the linguistic content and / or its modification. Some measures involving the parameters frequency, intensity and duration prosodic cues are important in the expression of attitudes in speech. The present study aimed to analyze how the parameters behave in prosodic expression of the attitude of irony. To this end, we selected 9 students of performing arts at the end of the course, all male residents in the city of Belo Horizonte, with ages ranging from 18 to 35 years. Each informant was instructed to issue statements expressing the attitude of irony. The issuance of these statem ents was held from 15 carefully designed situations, so that the respondents felt the need to express the attitude of irony. Besides the attitude, the informants were also asked to record the reading of the situation, to be used as a reference for analysis . Data collection and analysis were performed on acoustic PRAAT ® program, version 5.1.31. We analyzed the prosodic involving frequency, intensity and duration. The measurements were performed at the utterance of the accented vowel salient and interjections. For statistical analysis t test was used in addition to the assembly of the confidence interval for each parameter evaluated. The results revealed that the vast majority of parameters analyzed were higher values for the attitude of irony compared to reading. The attitude of irony is characterized by fundamental frequency (F0) end higher in relation to reading, while for the initial F0 no statistically significant difference between irony and reading. The F0 maximum and melodic breadth (AM) of the vowel of the accented vowel were more prominent in the attitude of irony than in reading and minimum F0 tone was higher in reading. The duration at both the statement and in the accented vowel prominent at higher levels in the attitude of irony. The analysis of interjections in the statements indicated that there was irony in the higher values for the parameters of minimum intensity, intensity variation, F0 minimum and texture of the interjection, but for the duration, maximum intensity, the variation of intensity , F0 maximum interjection and F0 mean difference was not statistically significant. Given the above, we conclude that the prosodic aspects had an influence on the expression of the attitude of irony. Similarly, we find that, in addition to intonation, parameters such as duration and intensity had an influence on the expression of the attitude studied.